The Role of the Educational Counselor in Countering Intolerance: A Field Study in Preparatory Schools in the City of Sulaymaniyah - حسين, ا.م.د. شوخان محمود حسين; سليمان, م. تارا محمود سليمان; Rashid, Dr. Sherine Ibrahim Mohamed Rashid (Sulaimani Journal for Humanities, 2026)
Intolerance is a major challenge in society, leading to discrimination, divisions, schisms, and the spread of violence. Because of the psychological and social barriers it creates, intolerance hinders the psychological development of individuals and pushes them toward turmoil. This negatively impacts social and cultural relations and prevents cooperation and mutual understanding among members of society. This challenge facing society must be confronted, especially in educational institutions, which are the places where future generations are nurtured and upon whom the openness of society and its acceptance of all that is new and modern depends. With the rise of intolerance and cultural tensions in middle schools, the educational counselor plays a vital role in creating a safe and tolerant learning environment. The counselor works to guide students to understand cultural and religious differences positively and enhance their ability to coexist peacefully with them. The counselor also provides psychological and social support to students to help them face the challenges that may arise as a result of intolerance and encourages them to think critically and constructively to contribute to building a diverse and tolerant society. Accordingly, the researchers decided to conduct this research, which consists of three chapters divided into several interconnected sections. The first chapter, the general framework of the research, defines the concepts and reviews previous studies. It includes three sections: the first section contains the general framework of the research, the second section defines the concepts, and the third section contains previous studies. The second chapter includes the theoretical framework of prejudice and the role of the educational counselor in confronting it. It is divided into two sections: the first section contains the theories that explain prejudice, its types, causes, and treatment, while the second section addresses the roles of the educational counselor in confronting prejudice in the school. The third chapter includes the research methodology and its field procedures through three sections: the first section contains the research methods, the second section contains the analysis of the field data, and the third section contains the recommendations and suggestions based on the research results.
Keywords: Educational counselor; school; intolerance; tolerance